Estimation of Voltage Sag Loss Based on Blind Number Theory - Fan Li-Guo; Zhang Yan-Xia (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Serious power quality issues and huge economic loss can be caused by voltage sag. It’s helpful for grid corporation to estimate voltage sag loss. Voltage sag and influence of sensitive equipment are analyzed in the paper. An estimation method of voltage sag loss based on blind number theory is proposed, which takes the sag magnitude and duration as its main characteristic parameters. First euclid distance and relative close degree between the sag magnitude and duration of voltage sag samples and threshold values is calculated based on TOPSIS. According to relative similarity degree，probable value, credibility and mean value of voltage sag loss are then calculated and influence of uncertainty factor can be considered. Example analysis shows that loss estimation method is a feasible and applicable for most sensitive equipments.